Influência dos parâmetros de secagem na viabilidade de Lactobacillus casei e nas propriedades de suco de laranja probiótico em pó - Alves, Niédila Nascimento (2016)
Probiotic foods contain live microorganisms able to confer health benefits. Most of probiotic foods are of dairy origin, which are not suitable for a significant portion of the population with restrictions on the consumption of lactose, milk protein and/or cholesterol. In this case, the development of non-dairy probiotic foods is useful. Currently, the literature presents some studies involving the development of probiotic fruit and vegetable juice. The large amount of water present in the juice results in transport and storage costs, in addition, refrigeration is necessary to maintain the probiotic microorganism viability. Thus, the objective of this work was to study the influence of spray and spouted bed drying processes on the viability of the probiotic microorganism Lactobacillus casei and on the physicochemical characteristics of powdered probiotic orange juice. The drying parameters for spray dryer (feed flow rate) and spouted bed (feed flow rate and drying temperature) were studied, using maltodextrin and gum Arabic as drying agents. It was also conducted the storage at room temperature of the product obtained the spouted bed. The viability of the probiotic microorganism was quantified immediately after drying and during storage. The physicochemical quality of the product was evaluated from the measurement of moisture, aw, Tg, particle size, rehydration time and morphology. The results showed that the viability of the probiotic microorganism was higher after spouted bed drying (about 9 log CFU / g) than after spray drying (about 5 log CFU / g). The powdered products obtained by both processes showed acceptable physicochemical characteristics. However, the samples produced by spray drying showed higher Tg, lower aw and moisture. The temperature increase since 80 °C, in the spouted bed drying, and the amount of residual water in the powder product produced at 60 °C reduced the probiotic microorganism viability during storage. The probiotic juice in powder produced at 70 °C showed a final viability of 6.7 log CFU/g in 5 weeks of storage. Among the parameters tested, the spouted bed drying at 70 °C of temperature, using maltodextrin with intermediate dextrose equivalent (DE20), proved to be more appropriate for the production of powdered probiotic orange juice.